Yield and quality of fodder oat (Avena sativa) and barley (Hordeum vulgare) at various stages of harvesting - Hussain, Ashiq; Khan, Sartaj; Mohammad, Dost; Bhatti, M Banaras; Mufti, M Usman (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1990 and 1991 to evaluate yield und quality of fodder for various harvesting stages in oat (Avena sativa L.) and barley (Hordeum vulgare L. Sensu lato). The stages or harvesting were: repeated cutting of plants al 4-leaf, tillering, jointing and booting stages and harvesting of plant once at ear emergence, 50% flowering, 100% flowering, early milk and early dough stages. Oat harvested at hooting stage and barley at 100% flowering stage gave the maximum green fodder yields (79.45 and 63. 10 tonnes/ha respectively). In oat and barley crops, the highest dry matter yield (15.54 and 13.75 tonnes/ha respectively) was recorded at early dough stage, In both the crops crude protein contents decreased with the advancement in crop maturity. The maximum crude protein content (14.93 and 14.37% in oat and barley respectively) was observed when the crops were cut repeatedly at 4-leaf stage, whereas the minimum at early dough stage in both the crops. Oat and barley harvested at booting stage proved better for reasonable grecn-fodder yield (67.32tonl1~s/lm), dry- maller yield (11.66 tonncs/ila) and foddt:r quality (crude protein 10.33%,). At this stage sufficient quantity of fodder yield with moderate quality was obtained in both the crops.